PERAN DAN UPAYA BAPEPAM DALAM MENCEGAH KECURANGAN PADA LAPORAN KEUANGAN PERUSAHAAN OLEH AKUNTAN PUBLIK - Arya Wahyudi Karditha, Inocencio; Putrawan, Suatra (Kertha Semaya : Journal Ilmu Hukum, 2013)
Public accountant is a proffesion that support capital market, who has legal right to audit every financial report of a firm. But nowadays this proffesion is being noticed because it takes a role to do some violations both data manipulation and any frauds on financial report. Bapepam as supervisor institution of capital have a significant role to prevent every violationof the firm which is relevant to the public accountant proffesion that will impact creation of financial report without any frauds, besides this journal also explain Bapepam effort to prevent and detect any frauds on financial report by public accountant.
Keywords: Public Accountant, Manipulation Database,Fraud